Family Voting Rights, Board Characteristics, and Shareholder Value: Evidence from Indonesia - Saiful, Saiful (The Indonesian Journal of Accounting Research, 2011)
This study examines the relationship between board of director characteristics and shareholder value. This study also investigates the moderating role of family voting rights on the relationship between proportion of independent members on board and shareholder value. Based on 88 samples of Indonesian listed companies for the period 2002 to 2005 (352 observations) and using random effect panel data analysis, the results showed that the proportion of independent members on board is positively and significantly associated with shareholder value. It means that the role of an independent board director in advising and monitoring management to act in the best interest of shareholders is effective whether in a developed or in developing market including Indonesia. Further, this study also found that a lower proportion of family voting rights leads to the strengthening of the positive relationship between independent board and shareholder value.